Psychological Health of Primary Caregivers: An Association of Primary Caregiver’s stress and Depression with Behavior Severity of Autistic Children - Zeenaf Aslam, Mansoor Ghani, Samina Kausar, Shazia Maqbool, Farhan Mukhtar, Mahpar Qama, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the prevalence of stress and depression among primary caregivers and determine its association with the behavior severity of children with Autism. Study design: Cross-sectional, analytical study using non-probability purposive sampling Place & duration: The study was conducted at the department of Developmental & Behavioral Pediatrics of Children Hospital, WAPDA teaching hospital complex, and Global Institute for Autism and Special Needs, Lahore 1st March to 1st Oct 2020. Methodology: Primary caregivers include the mother, father, and grandparents/siblings (n=96) of children confirmed diagnosed with Diagnostic and Statistical Manual-TR (DSM-IV),who were attending to behavior, sensory and speech therapies of their autistic children. To assess stress and depression; self-administered, structured questionnaires Parenting Stress Scale (PSS) and Beck Depression Inventory (BDI-0) were used respectively. Results: The current study highlighted that, overall, mean stress score was 52.3±7.3,rangingfrom 36.0 to 70.0, and the depression score was 62.5%, where 25% mildly, 11.5%borderline/clinical,16.7% moderately and 9.4% were severely depressed. Likewise, mothers 76(79.2%) are more embedded in caregiving responsibilities of their child with autism and reported more pronounced level of stress as compared to fathers (p=0.003). Conclusion: The prevalence of depression was foundhigher than stressamongprimary caregivers. These studyfindings are crucial for Sustainable Development Goals by the United Nations (SDG-3); to ensure healthy lives and to promote the well-being of all, all ages. Keywords: Stress, Depression, Parents, Autism Spectrum Disorder, Developmental Disability